Heartbeat: Glycaemic control and excess risk of major coronary events in type 1 diabetes. - Rahimi, K; Otto, CM (BMJ Publishing Group, 2017)
Individuals with diabetes are known to be at increased risk of cardiovascular events. However, most studies to date have focused patients with type 2 diabetes. In this issue of Heart, Matuleviciene-Anängen and colleagues1 report the findings of a study that investigates the risk of myocardial infarction in patients with type 1 diabetes compared with matched controls in Sweden. The focus on type 1 diabetes is particularly valuable given that (unlike type 2 diabetes) its diagnosis commonly precedes the development of other potentially confounding or mediating risk factors for cardiovascular disease. With about 1500 cardiovascular events during 8 years of follow-up, the researchers show that patients with type 1 diabetes have a four times higher risk of non-fatal myocardial infarction or coronary death. The excess risk was diminished but did not disappear in those with good glycaemic control or when there was no renal dysfunction at baseline. In addition, women were found to be at higher risk of cardiovascular events at every age category investigated.